Les Amazones : des phobies masculines aux rêves de femmes… - Frédérique Verrier (Laboratoire Italien)
The article highlights some of the manipulations and mystifications that surround the Amazons, quintessential example of warrior women, in the treatises on “phylogyny” and in 16th century epic. This –non exhaustive– study stems from a more systematic investigation on the comparison between the various rhetorical uses of the warrior women (in biographies, treatises, historiography, epic).